Handbook of State Aid for Film Finance, Industries and Regulation (Media Business and Innovation,, 2018)
This book is an analysis of the specificities of public film funding on an international scale. It shows how public funding schemes add value to film-making and other audio-visual productions and provides a comprehensive analysis of today's global challenges in the film industry such as industry change, digital transformation, and shifting audience tastes. Based on insights from fields such as cultural economics, media economics, media management and media governance studies, the authors illustrate how public spending shapes the financial fitness of national and international film industries. This highly informative book will help both scholars and practitioners in the film industry to understand the complexity of issues and the requirements necessary to preserve the social benefits of film as an important cultural good.